Playing With Dreams - Workshop Playing Cards - Wang, Irina; Rasmus, Sirpa; Sarkki, Simo; Habeck, Otto; Burgess, Philip; Pekkarinen, Antti-Juhani; Eronen, Jussi (Zenodo, 2023)
This is a guide for facilitating future-oriented workshops in order to gather insight for research and support long term planning in nature-based livelihoods. Attached are also the self printingplaying cards in multiple languages for use in the person workshops. These are provided in English, Finnish, Norwegian, North Sámi, Swedish and Norwegian. Attached are also instructions on how to print the playing cards for best results. Irina Wang was the lead designer. Developing more narratives around Arctic futures can help local communities, policy makers, and other actors anticipate plausible developments/surprises, understand ongoing dynamics, and aid in decision making. This workshop is designed to help articulate and develop the following aspects of scenario work: Systems understanding of past, present, and future dynamics Response and adaptation to plausible surprises that may unfold Desirable futures for stakeholders and decision makers to strive toward Time estimates given in this document are only suggestions. Depending on the particular needs of each project and the nature of its inquiry, each part of the workshop can be amplified or de-emphasized. For instance, Part III focuses on imagination and backcasting, articulating actionable steps towards various preferred futures. This can work as a brief closure to Parts I and II, or modified to be the main workshop focus by adding more detailed prompts and designating more time at each step. The downloadable files include a facilitation guide, assembly instructions, and print-ready stickers (available in English, North Sámi, Finnish, Norwegian, Swedish, or as a blank template). Our warmest thanks to all workshop participants and support for workshops that was received from the Natural Resources Institute Finland (Luke) and the Finnish Reindeer Herders' Association. We would like to thank Lapland University of Applied Sciences in Rovaniemi and Sámi Education Institute in Inari for invitations to pilot the workshop with their students. Mikko Jokinen, Ilona ...